Tinjauan Hukum Humaniter Internasional dalam Operasi Enduring Freedom Amerika Serikat ke Afghanistan dan Peran International Criminal Court (ICC) - Ismadi, Reno; Putranto, Awatar Bayu; Pratiwi, Tiffany Setyo (Nation State: Journal of International Studies, 2019)
The US military invasion to Afghanistan took place when the War on Terror declared by the United States after the incident in September, 2001 at World Trade Center. One of the military operations in this invasion was called Enduring Freedom. This research will discuss the violations committed by America in the invasion of Afghanistan, particularly during the Enduring Freedom operation, which it was reviewed through Geneva Law and The Rome Statute. The author using literature studies with qualitative methods. The author found that the violations of the Geneva Conventions of 1949 and The Rome Statute Article 8 and 11 were carried out by America during the deliberate Enduring Freedom Operation. The violation was proven but the International Criminal Court (ICC) did nothing.